2010
DOI: 10.1039/c005296e
|View full text |Cite
|
Sign up to set email alerts
|

Integration of single oocyte trapping, in vitro fertilization and embryo culture in a microwell-structured microfluidic device

Abstract: In vitro fertilization (IVF) therapy is an important treatment for human infertility. However, the methods for clinical IVF have only changed slightly over decades: culture medium is held in oil-covered drops in Petri dishes and manipulation occurs by manual pipetting. Here we report a novel microwell-structured microfluidic device that integrates single oocyte trapping, fertilization and subsequent embryo culture. A microwell array was used to capture and hold individual oocytes during the flow-through proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 25 publications
0
94
0
Order By: Relevance
“…Arrays of 1-mm-thick polydimethylsiloxane nanowells (50 μm) were manufactured by replica molding using a custombuilt mold, adhered directly to a 3 in ×1 in glass slide, and sterilized in an oxygen plasma before use (41). anti-CD28 and anti-CD49d for 5 h. Stimulated cells were counted and adjusted to a density of 1 × 10 6 cells/mL A 300-μL aliquot of the cells was deposited onto a sterilized array of nanowells.…”
Section: Methodsmentioning
confidence: 99%
“…Arrays of 1-mm-thick polydimethylsiloxane nanowells (50 μm) were manufactured by replica molding using a custombuilt mold, adhered directly to a 3 in ×1 in glass slide, and sterilized in an oxygen plasma before use (41). anti-CD28 and anti-CD49d for 5 h. Stimulated cells were counted and adjusted to a density of 1 × 10 6 cells/mL A 300-μL aliquot of the cells was deposited onto a sterilized array of nanowells.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of fertility, traditional channel-based devices have been developed for sperm selection (18 -22 ), embryo development (23)(24)(25), and semen analysis (14, 26 -28 ). Recently, paper has emerged as a scalable diagnostic platform (29 -32 ).…”
mentioning
confidence: 99%
“…Microfluidic IVF/CI in animal model studies has also emerged as a step in the process of 'LOC' IVF. A sophisticated microfluidic device was used for trapping (spatially maintaining) mouse oocytes, motile sperm isolation, microinsemination and embryo development for 96 h (Han et al, 2010). This report demonstrated that all these steps in the mouse IVF process could be performed on a single device.…”
Section: Conventional Inseminationmentioning
confidence: 98%
“…In addition, an in silico modelling experiment was performed to begin explaining potential mechanisms of benefit of culturing in a microfunnel with dynamic media flow compared with microchannels with gravity flow (detrimental to embryo development; Hickman et al, 2002). Han et al (2010) also reported a microwell structure microfluidic device that performed multiple steps of the IVF process. Using mouse embryos they demonstrated that this microfluidic cartridge could trap oocytes in microwells, integrate insemination and fertilization and support embryo development to the blastocyst stage.…”
Section: Embryo Culture With Microfluidicsmentioning
confidence: 99%